The qualities of leadership: direction, communication, and obfuscation - Myatt, D; Dewan, T (University of Oxford, 2007)
Party activists wish to (i) advocate the best policy and yet (ii) unify behind a common party line. An activist's understanding of his environment is based on the speeches of party leaders. A leader's influence, measured by the weight placed on her speech, increases with her judgement on policy (sense of direction) and her ability to convey ideas (clarity of communication). A leader with perfect clarity of communication enjoys greater influence than one with a perfect sense of direction. Activists can choose how much attention to pay to leaders. A necessary condition for a leader to monopolize the agenda is that she is the most coherent communicator. Sometimes leaders attract more attention by obfuscating their messages. A concern for party unity mitigates this incentive; when activists emphasize following the party line, they learn more about their environment.